Automated visual inspection (AVI) research for quality control in metal stamping manufacturing - Habibullah, Akbar; Anton Satria, Prabuwono (2008)
This paper presents a set of techniques in Automated Visual Inspection (A Vl) system to perform qnality control for metal stamping industry. AV/ system is aim to confirm whether a product match its quality standard and requirement or not. The system consists of 2D image sensor, lighting system, computer, image processing routines, networking, and handling mechanism. The system is expected to be integrated in the over all process in industry. This paper is focusing to the algorithm aspects of the A VJ system. ft consists of digital image acquisition, noise reduction, edge detection, feature extraction and classification. The result shows the potential implementation to improve the quality control in manufacturing environment.